Dialect Dictionary as a Source of Texts of Ethnic Knowledge - Ragaišienė, Vilija (Vilnius University Open Series, 2021)
The article examines the specifics of the preparation of dialect dictionaries – the goal and purpose, the principles of material selection and presentation. The research carried out shows that a comprehensive dialect dictionary must present the totality of words used in a dialect and reflect the most important distinguishing features of the dialect – phonetic, accentual, morphological, syntactic, semantic and stylistic fields of data. Therefore, when collecting material for a future dictionary, it is necessary to take into account three important things: 1) method of data collection, 2) themes of oral and written texts, 3) principles of compiling a database.Properly selected illustrative sentences of a comprehensive dialectal dictionary are meant to reveal the so-called microstructure of a dictionary entry, and show a broader structure of the concepts researched than demonstrated in the lexicographic definition of words.A dialect dictionary is a cultural and historical phenomenon that records the level and peculiarities of the knowledge of the world of an ethnic group at a certain period of time. Texts reveals people’s ethnic values, their attitudes towards social and religious relationships, everyday phenomena, etc. Therefore, a comprehensive dialect dictionary is to be considered as a multi-layered text of ethnic knowledge, revealing the heritage of material and spiritual culture passed down from generation to generation by a particular ethnic group. A dictionary like this regulates the most important areas of man’s life: establishes the rules of behaviour and etiquette, describes customs, provides knowledge about folk remedies and economic activities, explains world phenomena, provides fragments of mythical worldviews and so forth.
Keywords: comprehensive dialect dictionary; dictionary entry; word meaning; illustrative sentence; concept; worldview; text of ethnic knowledge